Genomic analysis of multidrug resistant qnrD-harbouring Morganella morganii with zoonotic transmission potential - Jones-Dias, Daniela (2017)
Study Purpose: Morganella morganii is a Gram-negative bacteria from the Enterobacteriaceae family, usually prevalent as a human commensal organism. In this study, we aimed to investigate the molecular background sustaining multidrug resistance and pathogenicity in an avian M. morganii isolate. Methods: M. morganii INSLV892 was recovered from 13-day old broilers belonging to a poultry industrial unit during post-mortem examination. The isolate was tested for its antimicrobial resistance and found to be non wild-type to ampicillin, ciprofloxacin, tetracycline, chloramphenicol and trimethoprim, which is consistent with multidrug resistance. Whole genome sequencing was performed on a MiSeq (Illumina) using 150 bp paired-end reads. Sequence reads were trimmed and filtered according to quality criteria, and assembled de novo using CLC genomics workbench version 8.0. A set of bioinformatic web tools were used to estimate the presence of pathogenicity determinants, antibiotic resistance genes, and clinically relevant mobile genetic elements within the M. morganii genome. Results: The assembly yielded 74 contigs, which together comprised 4,267,817bp. The genome sequence comprised 4,116 putative genes, among which 3,950 consisted of protein encoding sequences. In silico analysis of the antibiotic resistance genes revealed the presence of acquired resistance to aminoglycosides (aadA1y, aph(3')-Ic, and strA-strB), β-lactam (blaOXA-1), fluoroquinolones (qnrD, aac(6’)-Ib-cr), phenicols (catA2 and catB3), rifampicin (arr-2) sulphonamides (sul2), trimethoprim (dfrA1), tetracycline (tetY), and streptothricin (sat2). The qnrD antibiotic resistant gene was enclosed in an 8449bp length contig, displaying a mean coverage of 183.9-fold and a total read count of 13382. PHAST analyses identified 12 prophage regions and PathogenFinder estimated a 68.9% certainty of the isolate being a human pathogen. Conclusion: The detection of an avian M. morganii isolate harbouring multiple clinically important antibiotic resistance genes and pathogenicity factors raises concerns regarding the dissemination of infection in the food-chain and potential risk of zoonotic transmission.